Audit Quality as a Moderation Variable in Environmental, Social and Governance on the Financial Performance of IDX ESG Leaders Company - Rahma Wati; Indah Oktari Wijayanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The aim of this research is to investigate how Environmental, social, and Governance (ESG) factors impact financial performance, with consideration of Audit Quality, in companies listed on IDXESG Leaders. The study utilised secondary data from companies listed on IDX ESG Leaders. Quantitative methods were employed in this research. A purposive sampling approach was used to select companies based on specific criteria: (1) being listed on IDX ESG Leaders, and (2) consistently appearing on IDX ESG Leaders between 2021 and 2023. In this study, financial performance was considered as a dependent variable. Environmental, social, and ESG were identified as independent variables, while Audit Quality was treated as a moderation variable. The findings indicated a negative correlation between Environmental, Social, and Governance factors and the Financial Performance of IDX ESG Leaders companies, with no moderation effect being observed by Audit Quality. It is important to note that the study had limitations, including a small sample size of only 18 companies and the sole use of ROE as a measure for financial performance.